Effect of kinetic resistance training and technique on special strength level and effective kinematic variables in instep kick for soccer juniors - Shady, A. A. (International Journal of Kinesiology & Sports Science, 2016)
Background: Training with resistance is considered the essential and complementary part of players' preparation period during training season through developing different aspects. Objective: This study aims to investigate the Effect of Kinetic resistance training and technique on special power level and effective kinematic variables in instep kick for soccer juniors. Methodology: 20 junior soccer players (age: 17.54 ±0.5 years, body mass: 69.05 kg, height: 170 cm, training age=7.7 years) participated in this study were randomly assigned into two groups experimental (n=10) trained with kinetic resistance training program and technique and control (n=10) trained with traditional soccer training program only where, the experimental approach was used. Results: The kinetic resistance trainings and technique positively affected the special power level, kicking accuracy and time and effective kinematic variables in instep kick. Conclusion: The researcher recommended that coaches should give attention to special strength developing and to be an essential part of the training program through kinetic resistance trainings and technique. Also coaches should depend on the kinematic variables affecting performance for detecting the improvement level in performance as a result of kinetic resistance trainings and technique.